Ammonia volatilization from fertilizer sources on a loam soil in Idaho - Biswanath Dari (Wiley, 2021)
Abstract Optimizing crop N uptake while minimizing NH3 volatilization from N fertilizer sources is a critical part of agricultural best management practices. Urea is the most widely used N fertilizer but is also one of the most susceptible to losses as NH3. Fertilizer sources and additives can be used to reduce NH3 volatilization. Specifically, urease inhibitors [e.g., N‐(n‐butyl) thiophosphoric triamide (NBPT)] can reduce NH3 volatilization from urea. A novel fused ammonium sulfate nitrate (ASN) product has recently been developed as another potential alternative N fertilizer source but has not been studied widely. A field study was performed to quantify NH3 volatilization from the newly available ASN fertilizer as compared with various N fertilizers (ammonium sulfate [AS] and urea) including urea treated with the urease inhibitor NBPT in an alkaline calcareous loam soil in Idaho. Further, we assessed NH3 volatilization from surface applied and incorporated N fertilizers from these various N sources. Untreated surface‐applied urea volatilized the highest amount of NH3, whereas incorporation of N fertilizers was effective in reducing volatilization as compared with untreated surface‐applied urea. Our study indicated that the N fertilizer sources (AS, ASN, and urea+NBPT) were equally effective in reducing NH3 volatilization when compared with surface‐applied urea. Our study will help refine N fertilizer management under multiple field situations and traditional management practices of crop producers in the western United States. Further, site‐years and study locations would be needed to provide evidence of the effectiveness of ASN in reducing NH3 volatilization under a wider range of soil and environmental conditions.